The library of the Natal Provincial Council, 1858-1962 (Historia, 2021)
During  May  196~ the Natal Archives received one of the more valuableaccessions ever received by  an  Archive~j depot in  the  country  namely, thecontents q~the   Library   of  .the Natal  Provincial  Council,  totalling  some14,200 items in  all.    It  is  a  library."of upcommo~ interest to  the research-worker   in  a  large   numb~r  of  fields,   but   particul~cly    in  that   of  historicalinvestigation.The  intention of. the  Natal Legislative Council was to  build  up a  com-plete  library  -reference section and  all  -and so  books covering  allaspects of  life   in  which  legislators  might  conceivably be  interested wereordered  from   England   and  bound  there  in  leather  before  being  shipped  toNatal.   The Legislative Council, and  later the  Natal  Parliament, voted  anannual sum of  money for  its  upkeep until  Union  in  1910;  after  1910 thiswas discontinued but  all  government publications were sent to  the  libraryfor  the  purposes  of  record.The  result is  that the Library  is, as a visiting  librarian  remarked envi-ously "both  a museum-piece and a  window on the Victorian and Edwardianworlds."   Captured within  it is the world  as the "Victorian and the Edwardiansaw it.    For  as many aspects as  it  was possible to  encompass within  theconfines  of   a  fairly    small   reference  library    are  represented  here.    Thereare  books on:   Fiction,  Essays, Letters, Biographies, Geography, Geology,Anthropology,  Entymology, History   (Ancient  and  Modern),  Useful  Arts,Fine  Arts,  Architecture, Agriculture,  Botany, Law,  Tribal  Wars,  Religion,Politics, Dictionaries, Who's Who  (British and South African),  South Africanand Overseas Directories, Railway  Engineering, Poetry, Literature, Encyclo-paedias and  Periodicals, to  mention a  few  taken at  random.   There is  ofcourse a  host of  other subjects as well.Perhaps the best description of  the  library  was given in  1955, when itwas reported to  consist of:  Statutes, Votes and  Proceedings, etc.  (of  S.A.,U.K.  and other countries), Reports of  Committees, Blue  Books, Directories,Whitaker's, Who's Who, Law Books, etc., also much biography, some travel,Africana, hobbies, agriculture, natural  science, sociology, etc., much fiction,poetry, essays, etc
Keywords: Natal Provincial Council; Law collection; Colonies; Library